the 39 clues: beyond the grave (book 4) - Watson, Jude; Jude Watson (New York Scholastic, Inc., 2009)
In Beyond the Grave (Book 4) by Jude Watson, Amy and Dan Cahill travel to Cairo, Egypt, to find the next clue, uncovering secrets about their grandmother Grace's past and the Ekaterina branch. Pursued by ex-KGB agent Irina Spasky, they navigate traps, a secret Ekat stronghold, and threats from rivals Bae Oh and Jonah Wizard.
English